(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This study explores the spatial distribution of tourism resources in the Samarkand region using Geographic Information Systems (GIS) and predictive modeling. It identifies key tourism attractions, infrastructure, and natural resources, focusing on the disparities between Samarkand city and surrounding districts. The research highlights the potential for eco-tourism in underutilized areas, such as Mironkul and Okhalik, while also addressing the need for improved infrastructure. The findings provide valuable insights for policymakers and investors aiming to develop sustainable tourism in the region